Editorial Preface - Yunus, Riduan; Ismail, Al Emran; Ibrahim, Nabilah (International Journal of Integrated Engineering, 2019)
The 11th regular issue, number 8 is presenting the latest findings and research in the three major engineering field, namely, Civil and Environmental Engineering, Electrical and Electronic Engineering, and Mechanical, Materials and Manufacturing Engineering. The chief editors really appreciate support and contributions from the Editorial Board and Reviewers for making the process of selection of articles rigorous and meeting the high standard of scholarship that had been set. There are 31 articles were selected to be published in this issue, which reflects the niche of IJIE. Hopefully, the articles will provide additional information and contribute to the development of the engineering field. The chief editors strongly encourage authors to submit their articles and readers to provide feedback. Any comment for improvement is really appreciated. Please visit IJIE website http://penerbit.uthm.edu.my/ojs/index.php/ijie/ to access the online version of this issue along with archived editions. The chief editors also would like to thank all the authors who have contributed manuscripts in IJIE and those who are awaiting their manuscripts for publication in subsequent issues.